Implementasi Pemberian Hadiah Pada Tabungan Hijrah Prima Berhadiah Menurut Fatwa DSN-MUI - Ulfa Nur Sakinah; Mujibno, Mujibno (Jurnal Ekonomika dan Bisnis Islam, 2023)
One of the Islamic banks that implements the prize program is Bank Muamalat Indonesia, which is the Hijrah Prima Savings wit Prizes program. Mud}a>rabah contracts generally only provide profit sharing in the form of a ratio, interestingly in this savings customers don’t only get profit sharing. Customers will also get prizes at the beginning as desired without being drawn. However, customers who cancel the hijrah prima savings program with prizes before the agreement period will be charged a prize replacement fee. This research uses field qualitative methods (field research). Data sources are obtained from primary data sources and secondary data through interview, observation, and documentation techniques. The data analysis techniques used are data reduction, presentation of conclusion drawing data. To check the validity of the data using triangulation techniques. The results of this research said that the implementation of giving gifts to hijrah prima savings with prizes at Bank Muamalat Indonesia KCP Sumenep is that banks given gifts in the form of goods to customers of hijrah prima savings with prizes. In this case, DSN-MUI allows the awarding of such gifts as stipulated in DSN-MUI fatwa No: 86/DSN-MUI/XII/2012 concerning gifts in raising funds, for which the bank has added one of the conditions for a loan-use agreement when giving gifts.